Hierarchically Structured Zn-Al LDH/Hydrochar from Rambutan Peel (Nephelium lappaceum L.) for Enhanced Fe(II) Adsorption - Erviana, Desti; Normah, Normah; Arieveali, Heroldinho; Ramadhan, Navinda (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
Dissolved ferrous ions in water pose significant environmental and operational challenges, necessitating efficient and sustainable removal technologies. In this study, a hybrid adsorbent was developed by integrating Zn-Al layered double hydroxide (LDH) with hydrochar derived fromrambutan peel (Nephelium lappaceum L.) via coprecipitation. Characterization confirmed successful composite formation with a substantial increase in specific surface area from 9.621 m2.g-1 for pristine Zn-Al LDH to 52.964 m2.g-1 for the composite, accompanied by enlarged pore volume and enriched oxygen-containing functional groups. Batch adsorption experiments showed strong pH dependence, with optimal Fe(II) removal at pH 6 and equilibrium reached within 120 min. The Zn-Al LDH@NL-HC composite exhibited a markedly higher adsorption capacity (51.501 mg.g-1) compared with Zn-Al LDH (15.692 mg.g-1) and hydrochar alone (8.594 mg.g-1), indicating a significant synergistic effect. Isotherm analysis revealed a maximum adsorption capacity of 76.336 mg.g-1 at elevated temperature, while kinetic data followed a pseudo-second-order model, suggesting chemisorption-dominated uptake. Thermodynamic parameters indicated an endothermic and spontaneous process. Regeneration studies demonstrated excellent stability, with adsorption efficiency maintained at 79.48% after five cycles. The superior performance is attributed to combined mechanisms including electrostatic attraction, surface complexation with oxygen-rich groups, ion exchange within LDH interlayers, and diffusion into mesoporous structures. These findings demonstrate the effective valorization of agricultural waste into a high-performance and reusable adsorbent for Fe(II) remediation in aqueous systems.